EFFECTIVENESS OF THE ROLE OF THE SHARIA SUPERVISORY BOARD IN GOOD CORPORATE GOVERNANCE PERFORMANCE - Huda, M. Ikhwanul; Mujib, Abdul (istinbath, 2025)
There is little doubt that sound corporate governance is the foundation for the quick rise of Sharia banks. One of Indonesia's most well-known Islamic banks is Bank Muamalat, which has grown significantly in popularity. Bank Muamalat Indonesia needs the Sharia Supervisory Board (DPS) to monitor its activities and ensure they align with sound corporate governance standards. Law No. 21 Article 32 of 2008, which strengthens PBI regulations, and Bank Indonesia Regulation No. 11/33/PBI/2009 are two further regulatory references that DPS uses for oversight. This study evaluates the efficacy of the DPS-implemented rules, namely Law No. 21 Article 32 of 2008 and Bank Indonesia Regulation No. 11/33/PBI/2009. This study uses normative legal research with a research approach using the statute approach and a conceptual approach. This study shows that due to the legal effectiveness carried out by DPS in its regulations, namely Bank Indonesia Regulation No. 11/33/PBI/2009 and Law No. 21 Article 32 of 2008, DPS has been quite effective in carrying out its duties by laws and regulations. This is evidenced by the implementation and absence of violations committed by DPS while carrying out their duties as supervisors. DPS Education Background is very influential in becoming a member of DPS. Unfortunately, in the GCG report of Bank Muamalat Indonesia, there is no mention of the development made by the institution in improving the competence of the National Supervisory Board.